Can the construction of ecological civilization pilot demonstration areas improve urban green total factor productivity? Evidence from China - Wu, Zijian; Fu, Lixiang (Frontiers in Environmental Science, 2025)
Improved urban green total factor productivity contributes to the enhancement of the global ecological environment and the promotion of sustainable development. This paper constructs a multiperiod double-difference model using a quasi-natural experiment and investigates the impact of constructing ecological civilization pilot demonstration areas on urban green total factor productivity based on data from 261 cities in China from 2007 to 2020. The results indicate that building ecological civilization pilot demonstration areas can elevate urban green total factor productivity, particularly in nonresource-based cities and medium-sized to large cities. The mechanism operates through two main channels: Enhancing government environmental concern and promoting the development of high-tech industries in the region. The findings of this study can offer Chinese insights for the global assessment of green city policies.